A highly contiguous genome assembly of the bat hawkmoth Hyles vespertilio (Lepidoptera: Sphingidae). Issue 1 (23rd January 2020) - Pippel, Martin; Jebb, David; Patzold, Franziska; Winkler, Sylke; Vogel, Heiko; Myers, Gene; Hiller, Michael; Hundsdoerfer, Anna K
Abstract: Background: Adapted to different ecological niches, moth species belonging to the Hyles genus exhibit a spectacular diversity of larval color patterns. These species diverged ∼7.5 million years ago, making this rather young genus an interesting system to study a wide range of questions including the process of speciation, ecological adaptation, and adaptive radiation. Results: Here we present a high-quality genome assembly of the bat hawkmoth Hyles vespertilio, the first reference genome of a member of the Hyles genus. We generated 51× Pacific Biosciences long reads with an average read length of 8.9 kb. Pacific Biosciences reads longer than 4 kb were assembled into contigs, resulting in a 651.4-Mb assembly consisting of 530 contigs with an N50 value of 7.5 Mb. The circular mitochondrial contig has a length of 15, 303 bp. The H. vespertilio genome is very repeat-rich and exhibits a higher repeat content (50.3%) than other Bombycoidea species such as Bombyx mori (45.7%) and Manduca sexta (27.5%). We developed a comprehensive gene annotation workflow to obtain consensus gene models from different evidence including gene projections, protein homology, transcriptome data, and ab initio predictions. The resulting gene annotation is highly complete with 94.5% of BUSCO genes being completely present, which is higher than the BUSCO completeness of the B. mori (92.2%) and M. sexta (90%) annotations. Conclusions: Our gene annotation strategy has general applicability to other genomes, and the H. vespertilio genome provides a valuable molecular resource to study a range of questions in this genus, including phylogeny, incomplete lineage sorting, speciation, and hybridization. A genome browser displaying the genome, alignments, and annotations is available at https://genome-public.pks.mpg.de/cgi-bin/hgTracks?db=HLhylVes1 .